Label Size Evaluation of Ready-To-Drink Beverages Based On Brand Knowledge Assessment with Brand Awareness as A Parameter - Brillian, Marcel; Kristina, Helena J.; Silalahi, Rudy V. (ASEAN Marketing Journal, 2021)
Manuscript type: Research Article Research Aims: Evaluate label size of RTD beverages based on brand awareness assessment to bridge the gap between marketing needs and environmental requirement. Design/Methodology/Approach: Interview, brand recognition experiment, brand recall questionnaire Research Finding: Propose some variation in percentage of label size reduction and show that larger label sizes do not ensure it will influence consumer’s ability and response time in recognizing products will be faster. Practitioner/Policy Implication: Label size reduction is a fine strategic implementation to initiate synergy between brand owners and recyclers toward sustainable waste management practice. Research Limitation/Implication: Label size reduction turns out to have positive implications for marketing side of the product.